(untitled) (ModaPalavra e-periódico, 2025)
Brazil is the fifth largest footwear producer in the world and the main producer outside the Asian region. This research aims to compare the production processes used in the production of traditional sneakers and sneakers with seamless rectilinear mesh uppers, in low complexity models (which require few operations in cutting and sewing the uppers). Through bibliographic, applied and qualitative research of an exploratory nature, this study compares the production flow, the time taken for the sneaker production, and the amount of textile solid waste generated by the respective processes. Although the experimental results of the case study are limited to two models of sneakers, produced by two different technologies, with one pair of sneakers of each model with its respective production process, the analyses indicated that in the production of the seamless knit upper sneakers, there is a reduction in production stages and in the amount of discarded solid waste. This suggests that companies adopting this new technology may gain a competitive edge.